Latest developments in MUC1 immunotherapy. (21st May 2018) - Taylor-Papadimitriou, Joyce; Burchell, Joy M.; Graham, Rosalind; Beatson, Richard
Abstract : Currently, there is renewed interest in attempting to recruit the host immune system to eliminate cancers, and within this renewed activity, MUC1 continues to arouse interest. MUC1 has been considered a possible therapeutic target for the past 30 years as it is up-regulated, aberrantly glycosylated and its polarization is lost in many adenocarcinomas. Moreover, MUC1 is expressed by some haematopoietic cancers, including acute myeloid leukaemia and myeloma. Although multiple clinical trials have been initiated and immune responses have been documented, effective clinical benefit worthy of approval for general application has not as yet been achieved. However, this does not appear to have quelled the interest in MUC1 as a therapeutic target, as shown by the increase in the number of MUC1-based clinical trials initiated in 2017 (Figure 1 ). As with all translational studies, incorporating new relevant research findings into therapeutic strategy is difficult. Decisions are made to commit to a specific strategy based on the information and data available when the trial is initiated. However, the time required for preclinical studies and early trials can render the founding concept not always appropriate for proceeding to a larger definitive trial. Here, we summarize the attempts made, to date, to bring MUC1 into the world of cancer immunotherapy and discuss how research findings regarding MUC1 structure and function together with expanded knowledge of its interactions with the tumour environment and immune effector cells could lead to improved therapeutic approaches.